Reception of Surah al-Kahf and its implementation in education in Indonesia - Rodliatin, Rodliatin; Mahsun, Mohamad; Najmuddin, Najmuddin; Rahman, Fuad (AJIS: Academic Journal of Islamic Studies, 2023)
To obtain a character who adheres to the Al-Quran in everyday life, students need to get used to it from an early age or it cannot be achieved with an instant process. Meanwhile, YPP Anwarul Ulum Keritang trains its students to get used to reading certain surahs at certain times, such as reading Al-Kahf every Friday night. However, in practice, it seems that students experience various obstacles so that their Fadhilah regarding reading Surah Al-Kahf cannot be felt clearly. Therefore, this research explores the motivation of students at YPP Anwarul Ulum in reading Surah Al-Kahf and describes the obstacles they experience in carrying out the routine of reading the Al-Quran at YPP Anwarul 'Ulum. Furthermore, this research also explored participants' manners in reading the Qur’an. This research took a sample of 99 participants. Data mining was carried out by applying written interviews and preliminary questionnaires. Participants' responses and arguments were then processed using Nvivo 12 software. This research found that 60% of participants were motivated to follow the routine of reading Al-Kahf because of the priority/fadhilah of reading it. Meanwhile, the obstacles that most often occurred to participants were situations of hadas, drowsiness, self-control, and lust which still had to be trained. This research also found that not all etiquette in reading the Qur’an had been implemented by the participants. Therefore, this study recommends to participants in particular and every Muslim, in general, to practice self-control and lust and apply all manners in reading the Qu’ran.